Urban Fringe Bushwalking: Eroding the Experience - Hughes, M.; Tye, Marian; Chandler, P. (Taylor & Francis, 2016)
Urban fringe areas are vital resources for urbanized populations, but are under pressure to meet demand for a variety of land uses, including recreation. Bushwalking is a form of nature-based recreation experience founded on antiauthoritarianism, egalitarianism, and immersion in the Australian bush. An online and telephone survey gathered perceptions of bushwalking club members regarding their experiences on the urban fringe in Western Australia. Results reveal perceptions that the bushwalking experience is being eroded due to confinement into “tame” settings. Respondents perceived themselves as custodians of nature subject to inconsistent, unfair management treatment, fueling an existing bushwalker suspicion of authority. The article poses a challenge for urban fringe natural resource managers to harness the potential of bushwalking club members by overcoming negative perceptions and sharing common goals. The implication is that certain types of recreation could represent a natural resource management asset, rather than a threat to be managed.